Question
upstudy study bank question image url

Find the derivative of the following function. \[ y=\frac{\left(2 x^{2}+4\right)(3 x+1)}{4 x-3} \]

Ask by Kelly Norton. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The derivative of \( y=\frac{(2x^2+4)(3x+1)}{4x-3} \) with respect to \( x \) is \( \frac{12x^2 + 12x + 12}{(4x-3)^2} \).

Solution

The derivative of the function \( y=\frac{(2x^2+4)(3x+1)}{4x-3} \) with respect to \( x \) cannot be calculated using the current method. If you need to find the derivative, please provide the function in a different format or specify the variable with respect to which you want to find the derivative.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the derivative of \( y = \frac{(2x^2 + 4)(3x + 1)}{4x - 3} \), we can use the quotient rule, which is given by: \[ \frac{d}{dx} \left( \frac{u}{v} \right) = \frac{u'v - uv'}{v^2} \] Here, let \( u = (2x^2 + 4)(3x + 1) \) and \( v = 4x - 3 \). First, we need to compute \( u' \) and \( v' \). 1. **Finding \( v' \)**: \[ v' = \frac{d}{dx}(4x - 3) = 4 \] 2. **Finding \( u' \)**: For \( u = (2x^2 + 4)(3x + 1) \), we will use the product rule: Let \( a = 2x^2 + 4 \) and \( b = 3x + 1 \). - Find \( a' \): \[ a' = \frac{d}{dx}(2x^2 + 4) = 4x \] - Find \( b' \): \[ b' = \frac{d}{dx}(3x + 1) = 3 \] - Apply the product rule: \[ u' = a'b + ab' = (4x)(3x + 1) + (2x^2 + 4)(3) \] Expanding this: \[ u' = 12x^2 + 4x + 6x^2 + 12 = 18x^2 + 4x + 12 \] 3. **Putting it all together**: Now we can use the quotient rule: \[ y' = \frac{(u'v - uv')}{v^2} \] Substitute \( u' \), \( v \), \( u \), and \( v' \): \( u' = 18x^2 + 4x + 12 \) \( v = 4x - 3 \) \( u = (2x^2 + 4)(3x + 1) \) \( v' = 4 \) Therefore: \[ y' = \frac{(18x^2 + 4x + 12)(4x - 3) - (2x^2 + 4)(3x + 1)(4)}{(4x - 3)^2} \] 4. **Simplifying**: To simplify the expression, you would expand both parts and then combine like terms. The final answer (derivative) is: \[ y' = \frac{(18x^2 + 4x + 12)(4x - 3) - 4(2x^2 + 4)(3x + 1)}{(4x - 3)^2} \] This will give the derivative of the function \( y \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy